Kerner's Folly, a house in Kernersville. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo made in the 1940s.
Kerner's Folly, a house in Kernersville.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth